In vivo key role of reactive oxygen species and NHE-1 activation in determining excessive cardiac hypertrophy - Cingolani, Oscar H. (2011)
Growing in vitro evidence suggests NHE-1, a known target for reactive oxygen species (ROS), as a key mediator in cardiac hypertrophy (CH). Moreover, NHE-1 inhibition was shown effective in preventing CH and failure; so has been the case for AT1 receptor (AT1R) blockers. Previous experiments indicate that myocardial stretch promotes angiotensin II release and post-translational NHE-1 activation; however, in vivo data supporting this mechanism and its long-term consequences are scanty. In this work, we thought of providing in vivo evidence linking AT1R with ROS and NHE-1 activation in mediating CH. CH was induced in mice by TAC. A group of animals was treated with the AT1R blocker losartan. Cardiac contractility was assessed by echocardiography and pressure–volume loop hemodynamics. After 7 weeks, TAC increased left ventricular (LV) mass by ~45% vs. sham and deteriorated LV systolic function. CH was accompanied by activation of the redox-sensitive kinase p90RSK with the consequent increase in NHE-1 phosphorylation. Losartan prevented p90RSK and NHE-1 phosphorylation, ameliorated CH and restored cardiac function despite decreased LV wall thickness and similar LV systolic pressures and diastolic dimensions (increased LV wall stress). In conclusion, AT1R blockade prevented excessive oxidative stress, p90RSK and NHE-1 phosphorylation, and decreased CH independently of hemodynamic changes. In addition, cardiac performance improved despite a higher work load.